2010
DOI: 10.1007/s11433-010-4129-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of additive NaN3 on the HPHT synthesis of large single crystal diamond grown by TGM

Abstract: In this paper, large single crystal diamond with perfect shape and high nitrogen concentration approximately 1671-1742 ppm was successfully synthesized by temperature gradient method (TGM) under high pressure and high temperature (HPHT). The HPHT synthesis conditions were about 5.5 GPa and 1500-1550 K. Sodium azide (NaN 3 ) with different amount was added as the source of nitrogen into the synthesis system of high pure graphite and kovar alloy. The effects of additive NaN 3 on crystal growth habit were investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…C N , in A-center form, is determined by an absorption coefficient of 1282 cm −1 which multiplies the absorption factor (16.5 atomic ppm per cm −1 ) after the IR spectrum is decomposed into two individual components according to the procedure described in Refs. [18] and [19]. C N , in C-center form, is obtained from an absorption coefficient of 1130 cm −1 , namely, 25.0 atomic ppm per cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…C N , in A-center form, is determined by an absorption coefficient of 1282 cm −1 which multiplies the absorption factor (16.5 atomic ppm per cm −1 ) after the IR spectrum is decomposed into two individual components according to the procedure described in Refs. [18] and [19]. C N , in C-center form, is obtained from an absorption coefficient of 1130 cm −1 , namely, 25.0 atomic ppm per cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…The concentrations of nitrogen in the form of A-center (N A ) and C-center (N C ) were calculated from the absorption coefficient which were multiplied by converting factor of 16.5 ppm/(cm -1 ) and 25 ppm/(cm -1 ) at 1282 cm -1 and 1130 cm -1 , respectively , after the spectra decomposed into two individual components using the procedure described in Ref. [7]. The calculation results with uncertainties around 5 % are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…[wt%] In Table 1, it is demonstrated that, with increasing the content of additive P 3 N 5 , the concentrations of nitrogen in the form of C-center and A-center are both gradually increased, and the highest value of total nitrogen concentration can approach 2186 ppm, which is the much higher than those specimens doped with other nitride additive [7][8][9]. This result might be attributed to phosphorus decomposed from P 3 N 5 entering diamond lattice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different impurities have different influences on the properties of diamond crystals [1][2][3]. For example, by doping phosphorus and boron, n-type and p-type diamond crystals can be synthesized, respectively.…”
mentioning
confidence: 99%